HEIs service quality as a predictor of students’ satisfaction affecting academic performance: The extension of the Embryonic HESQUAL model - Kamrunnahar Happy; Nafiza Islam; Rabbir Rashedin Trin (Management Science Letters)
To question the dominanceof the dimensions of service quality using the embryonic HESQUAL model onstudents' satisfaction. Besides, the study will identify the mediating effect ofa department’s commitment and a moderating effect of self-efficacy on therelationship between students’ satisfaction and academic performance. The study was a one-time dimensionaland used a simple random sampling method which is suitable for quantitativestatistical analysis and homogeneous populations in nature. Analysis resultingfrom SmartPLS by using 431 responses from undergraduate and graduate students of public universities inBangladesh. The study found that students arefocused on core educational qualities and physical environmental facilities tobe satisfied. Thoroughly,students' satisfaction has a direct impact on academic performance butsurprisingly no moderating precedence of self-efficacy on the connectionbetween student satisfaction and academic performance was seen. Noticeably, theextension of the HESQUAL model of department commitment finds significant influenceson both satisfaction and academic performance. However, the modified HESQUEL will quantify thequality dimensions in higher education, and its application in this study candepict a greater understanding of the quality dimensions required to beprioritized by university authorities and policymakers.